2020
DOI: 10.19044/esj.2020.v16n22p139
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Structure on Financial Performance with Firm Size as a Moderating Variable of Non-Financial Firms Listed at the Nairobi Securities Exchange

Abstract: This paper examines the effect of capital structure on the financial performance of the non-financial firms listed at the Nairobi Securities Exchange and how this relationship is moderated by firm size. In addition, the paper evaluates the existence of equilibrium and disequilibrium relationship among the variables. The study analyzed unbalanced panel data sourced from across 53 non-financial firms listed at the Nairobi Securities Exchange which covers the period from 2010 to 2017. Total debt to total equity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this descriptive research whose target population comprised of all then eight companies that are listed under manufacturing and allied sector in Nairobi Security Exchange (NSE), it was found that retained earnings and equity have negative influence on profitability of firms studied. In another study by Meshack, Winnie, Okiro, and Ochieng (2022), the findings showed that capital structure had a positive statistically significant effect on profitability, hence the creation of the gap of study.…”
Section: Introductionmentioning
confidence: 93%
“…In this descriptive research whose target population comprised of all then eight companies that are listed under manufacturing and allied sector in Nairobi Security Exchange (NSE), it was found that retained earnings and equity have negative influence on profitability of firms studied. In another study by Meshack, Winnie, Okiro, and Ochieng (2022), the findings showed that capital structure had a positive statistically significant effect on profitability, hence the creation of the gap of study.…”
Section: Introductionmentioning
confidence: 93%
“…Further, although there are previous studies on IFR and firm value, the previous studies did not operationalize IFR into its six capitals (financial, manufactured, intellectual, human, social and environmental) which is the gap the current study sought to fill. Kerongo, Nyamute, Okiro and Duncan (2020) and Abbasi and Malik (2015) concluded that firm size has a moderating effect on value of listed firms at the NSE. This study also sought to confirm this assertion by investigate the moderating effect of firm size on the relationship between IFR and value of firms listed at the NSE.…”
Section: Introductionmentioning
confidence: 99%
“…If you choose an inappropriate capital structure, the company must bear the risks that will arise in the future [7]. Based on research Meshack et al [8] said that the capital structure affects financial performance. H2: Capital structure has a positive effect on company value Financial performance is an important indicator because it is used as a benchmark by investors to see the merits of a company or its financial position so that investors will consider more before investing their capital.…”
Section: Introductionmentioning
confidence: 99%